2017
DOI: 10.1021/acsomega.7b00550
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Oxygen Uptake and Vacancy Concentration in Pr-Doped CeO2

Abstract: The oxygen uptake of a series of Pr–CeO 2 materials was measured using thermogravimetric analysis at 420 and 600 °C, and at both temperatures, 20% Pr–CeO 2 was found to have the highest uptake. The materials were characterized using X-ray diffraction and scanning transmission electron microscopy. Defects in the materials were identified using Raman spectroscopy, and ultraviolet–visible spectroscopy was used to show the presence of Pr cations in the +3 oxidation sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…To confirm this, the O K -edge spectra of the CeO 2 NPs were compared and a large change was observed among the three different CeO 2 NPs unlike the XRD and Raman measurements, which had no structural change. Due to the large overlap of the O 2 p and Ce 4 f wave functions, the pre-edge peak (peak A) at the O K -edge yields the density of Ce 4 f states in CeO 2 NPs [ 39 , 40 , 41 ]. In other words, the O K -edge spectra ( Figure 1 c) confirmed that the intensity of peak A for the Cr@CeO x and Fe@CeO x NPs was smaller than that for bare CeO 2 NPs.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm this, the O K -edge spectra of the CeO 2 NPs were compared and a large change was observed among the three different CeO 2 NPs unlike the XRD and Raman measurements, which had no structural change. Due to the large overlap of the O 2 p and Ce 4 f wave functions, the pre-edge peak (peak A) at the O K -edge yields the density of Ce 4 f states in CeO 2 NPs [ 39 , 40 , 41 ]. In other words, the O K -edge spectra ( Figure 1 c) confirmed that the intensity of peak A for the Cr@CeO x and Fe@CeO x NPs was smaller than that for bare CeO 2 NPs.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2K, the Ce M 5,4 EELS spectra of CuCo−CeO 2 and CeO 2 show the presence of two Ce white lines, which are located at 884 and 902 eV because of the 3d 5/2 → 4f 7/2 (M 5 ) and 3d 3/2 → 4f 5/2 (M 4 ) electron transitions, respectively. 30 The chemical shift of the Ce M 5, 4 white lines and the relative-intensity ratio of these lines can be used to evaluate the redox properties of the CeO 2 samples. 10,31 Particularly, a higher intensity ratio of M 5 and M 4 peaks (IM 5 / IM 4 ) indicates a higher reducible nature.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, EELS experiments were also conducted to further investigate the valences of cerium ions on the CeO 2 surface. As shown in Figure K, the Ce M 5,4 EELS spectra of CuCo–CeO 2 and CeO 2 show the presence of two Ce white lines, which are located at 884 and 902 eV because of the 3d 5/2 → 4f 7/2 (M 5 ) and 3d 3/2 → 4f 5/2 (M 4 ) electron transitions, respectively . The chemical shift of the Ce M 5, 4 white lines and the relative-intensity ratio of these lines can be used to evaluate the redox properties of the CeO 2 samples. , Particularly, a higher intensity ratio of M 5 and M 4 peaks (IM 5 /IM 4 ) indicates a higher reducible nature. , According to the calculation results, the IM 5 /IM 4 ratio of CuCo–CeO 2 (0.8295) is higher than that of pure CeO 2 (0.7972), which indicates more Ce 3+ ions and a higher density of oxygen vacancies on the CeO 2 surface from the introduction of the Cu and Co dopants.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The Rietveld refinements were repeated on the basis of a multiple-cation partitioning (Table , column 4), leading to further improvement in the refinement quality criteria (blue symbols, Figure ). Cerium partitioning over the A and B perovskite sites was discounted on the basis of the higher energy required for the reduction of Ce 4+ to Ce 3+ as contrasted with the reduction of Pr 4+ to Pr 3+ …”
Section: Resultsmentioning
confidence: 99%